Control of CD nozzle flow using microjets at Mach 2.1 - Akhtar, Mohammad Nishat; Abu Bakar, Elmi; Aabid, Abdul; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences, 2019)
This paper reports the outcome of the wind tunnel investigation performed to study the effectiveness of the control jets to regulate the base pressure in an abruptly expanded circular pipe. Tiny jets four in a number, of 1 mm orifice diameter located at ninety degrees in cross shape along a pitch circle diameter (PCD) of 1.3 as a control mechanism were employed. The Mach numbers and the area ratio of the study were 2.1, and 4.84. The length-to-diameter (L/D) ratio of the duct tested was varied from 10 to 1. Nature of the flow in the duct, as well as static wall pressure distribution in the suddenly enlarged duct, was recorded. The main aim of this study was to assess the influence of the active control in the form of tiny jets on the flow field as well as the nature of the flow, and also the development of the flow in the duct. The results obtained in this study show that the flow field, as well as the wall pressure distribution, is not adversely influenced by the tiny jets. The minimum duct length seems to be 2D for NPR's in the range five and above. However, for all the level of expansion of the present study, the minimum duct length needed for the flow to remain attached seems to be 3D.